Maize Fungal Growth Control with Scopoletin of Cassava Roots Produced in Benin - Rafiatou Ba; Teou Alfa; Fernand Gbaguidi; Kosi Mawuéna Novidzro; Kokouvi Dotse; Koffi Koudouvo; Ursula Houngue; Marcel T. Donou Hounsode; Kossi Honoré Koumaglo; Yaovi Ameyapoh; Lamine Baba-Moussa (International Journal of Microbiology)
The chemical contamination of food is among the main public health issues in developing countries. With a view to find new natural bioactive products against fungi responsible for chemical contamination of staple food such as maize, the antifungal activity tests of scopoletin extracted from different components of the cassava root produced in Benin were carried out. The dosage of scopoletin from parts of the root (first skin, second skin, whole root, and flesh) was done by High Performance Liquid Chromatography. The scopoletin extract was used to assess the activity of 12 strains (11 strains of maize and a reference strain). The presence of scopoletin was revealed in all components of the cassava root. Scopoletin extracted from the first skin cassava root was the most active both as inhibition of sporulation (52.29 to 87.91%) and the mycelial growth (36.51–80.41%). Scopoletin extract from the cassava root skins showed significant inhibitory activity on the tested strains with fungicide concentration (MFC) between 0.0125 mg/mL and 0.1 mg/mL. The antifungal scopoletin extracted from the cassava root skins may be well beneficial for the fungal control of the storage of maize.